Histological differences in wound healing in Maxillofacial region in patients with or without risk factors (Bangladesh Journal of Pathology, 2009)
Maxillofacial surgeons often deal with many cases of delayed wound healing, some are related to known risk factors and some are unknown. This study was aimed to assess the histological features of wound healing on day 0 and day 7 in postoperative cases of maxillofacial region in patients with or without risk factors. Microscopic examination of tissue specimen is a reliable and reasonably safe method to evaluate the histological differences. Six known risk factors for delayed wound healing were studied, which are commonly associated with maxillofacial pathology. Both clinical and histological examinations were performed for the evaluation of 32 postoperative cases. Out of 32 patients, 17 patients with risk factor were in study group and 15 apparently healthy persons without risk factor were in control group. Postoperative clinical evaluation of wound was done at 3rd, 5th, 7th, 9th, and 11th day and histological examination of tissue specimen was done on day 0 and day 7. Based on six histological parameters, microscopic examination of tissue specimen was done by both routine Haematoxylin and Eosin stain and Masson's Trichrome stain. In day 7, healing wound of study group having risk factors showed profound amount of granulation tissue, early collagen fibres, plenty inflammatory infiltrate, vertical orientation of reticular pattern of collagen and minimum amount of mature collagen in majority of patients which indicates delayed healing. On the other hand, in control group majority showed horizontally oriented mature collagen fibres in fascicle. Statistically, significant association was found between study and control subjects in terms of pattern of collagen tissue, amount of early and mature collagen tissue at the 7th day of follow up. Clinical evaluation also had strong association with histological state of healing. Key words: Wound healing, Postoperative, Maxillofacial region. doi: 10.3329/bjpath.v24i1.2874 Bangladesh J Pathol 24 (1) : 3-8